Contribution of skin and stone to texture measurements of spherical model fruits - Rosenthal, Andrew J.; Lacresse, Alice; Voyer, Emmy (Wiley, 2018)
Fruits are composite materials often surrounded by a skin and sometimes containing rigid stones (pits). To understand the contribution of skin and stone to the overall texture of the fruit, model fruits were constructed from molded gelatin spheres, with rigid inclusions and a skin layer. Cross polarized light revealed the stress distribution during puncture testing and the mechanical measures of firmness, Poisson's ratio and breaking force were determined. Skin significantly raised the breaking force. Spherical stones raised the firmness—effectively reducing the deformable material in the sphere, resulting in inflated strains. Disc shaped stones compared with spherical ones, with the narrow edge normal to the force acted like an internal blade and significantly lowered the breaking force. Neither skin nor stone had any significant impact on Poisson's ratio. Three examples of real fruit (raspberries, grapes, and cherries) were tested to contextualize the findings.